2014
DOI: 10.1200/jco.2013.54.3769
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Regression Grading After Preoperative Chemoradiotherapy for Locally Advanced Rectal Carcinoma Revisited: Updated Results of the CAO/ARO/AIO-94 Trial

Abstract: Complete and intermediate tumor regressions were associated with improved long-term outcome in patients with rectal carcinoma after preoperative CRT independent of clinicopathologic parameters. This classification system needs to be prospectively tested in multiple data sets to validate its reproducibility in a wider setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
304
2
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 375 publications
(353 citation statements)
references
References 54 publications
27
304
2
11
Order By: Relevance
“…При II и III ста-диях рака прямой кишки (cT3/сТ4 или cN+) в боль-шинстве случаев стандартным подходом является со-четание хирургического лечения и неоадъювантной ХТ. Это позволяет значимо снизить частоту рецидивов, а по данным некоторых исследований, приводит к улучшению выживаемости [14,15]. По результатам лечебного патоморфоза определяется необходимость коррекции послеоперационной терапии [16].…”
Section: Discussionunclassified
“…При II и III ста-диях рака прямой кишки (cT3/сТ4 или cN+) в боль-шинстве случаев стандартным подходом является со-четание хирургического лечения и неоадъювантной ХТ. Это позволяет значимо снизить частоту рецидивов, а по данным некоторых исследований, приводит к улучшению выживаемости [14,15]. По результатам лечебного патоморфоза определяется необходимость коррекции послеоперационной терапии [16].…”
Section: Discussionunclassified
“…6,25,26 Another strategy, as suggested by Schrag,9 is to intensify the systemic treatment or to administer the systemic treatment earlier in the treatment course to prevent dissemination of micrometastases. The recent updated results from the German CAO/ARO/AIO-94 trial 27 showed a significant association between local treatment efficacy (TRG) and disease-free survival. Thus, it is likely that MRI volumetry of the primary tumour can predict systemic treatment response and therefore can be used to customize subsequent treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological tumor response (PTR), including tumor regression grade (TRG) and downstaging, has been indicated to be an important prognostic factor for LARC following CRT (6)(7)(8). PTR may be useful to stratify patients with different prognoses and to tailor surgical treatment strategies, particularly for sphincter-sparing candidates (9). Therefore, the early and accurate prediction of PTR is important.…”
Section: Introductionmentioning
confidence: 99%